Influence of Skeletal Bone Density on Dental Implant Stability in Patients with Osteoporosis (Latakia University Journal -Medical Sciences Series, 2023)
Osteoporosis is a major skeletal disease affecting millions of people worldwide. The disease predominantly affects postmenopausal females and is closely associated with aging. The aim of this study was to assess the effect of skeletal bone density on dental implant stability. The research sample included two groups: the study group consisted of (9) patients diagnosed with osteoporosis according to the T-Score scale, where their T-Score value smaller or equal -2.5 at ages 45-58 years, and the control group consisted of (9) individuals Healthy people aged 48-57 years.Patients in both groups received 18 dental implants and had implant stability measured by means of resonance frequency analysis (RFA) at implant placement and at prosthetic abutment placement (after 3 months of dental implant). The results showed that there were statistically significant differences in the dental implant stability values between the group of osteoporotic patients and the control group, as the low values of stability in the osteoporotic patients group indicate that the dental implant stability is affected by the skeletal bone density of the patient.